2019
DOI: 10.5194/acp-2018-1229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Source apportionment of highly time resolved trace elements during a firework episode from a rural freeway site in Switzerland

Abstract: <p><strong>Abstract.</strong> Trace element measurements in PM<sub>10</sub> were performed with 1 h time resolution at a rural freeway site during summer 2015 in Switzerland using the Xact multi-metals monitor. On average the Xact 625 elements (without accounting for oxygen and other associated elements) make up about 20 % of the total PM<sub>10</sub> mass (14.6 &#… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The abundance of elements K, Ba, and Br increased at the lockdown period. As known, K and Ba could be emitted by household fireworks for the traditional celebration during the Chinese Spring Festival) (Rai et al 2020 ; Yao et al 2019 ). Except for K, Ba, and Br, the mass concentrations of other elements showed declines in the lockdown period.…”
Section: Resultsmentioning
confidence: 99%
“…The abundance of elements K, Ba, and Br increased at the lockdown period. As known, K and Ba could be emitted by household fireworks for the traditional celebration during the Chinese Spring Festival) (Rai et al 2020 ; Yao et al 2019 ). Except for K, Ba, and Br, the mass concentrations of other elements showed declines in the lockdown period.…”
Section: Resultsmentioning
confidence: 99%
“…Se and As are tracers for the coal burning sources (Cui et al, 2019). Rai et al (2020), Cai et al (2017), and Chang et al (2018) reported that Pb and Fe are mainly derived from steel industry or smelter. Liu et al (2019) suggested that Co originate from the metal industry sources, and Cr is widely used in electroplating and leather industries.…”
Section: Sources Of Dissolved and Total Fementioning
confidence: 99%
“…Factor 5 was characterized by high loads of Cr, Co, Ni, Cu, Sr, Ba, and Pb, indicating non-combustion related industrial emission (Cai et al, 2017;Chang et al, 2018;Liu et al, 2019;Rai et al, 2020). High loads of Cr, Mn, Cu, Zn, Se, Pb in factor 6 suggested traffic emission (Alias et al, 2020;Lin et al, 2015).…”
Section: Pmf Analysismentioning
confidence: 99%